Preparation method of Ti4O7 doped high-emissivity film layer

Through multi-arc ion plating, microarc oxidation and hydrothermal treatment processes, a high emissivity Ti4O7 doped film layer is constructed, which solves the problem of anode cylinder structure failure caused by high temperature of the ion propeller and achieves efficient heat dissipation.

CN119553333APending Publication Date: 2025-03-04XIAN SURFACE MATERIAL PROTECTION CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411719957.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, the high temperature of the ion thruster causes the anode cylinder structure to be out of order, and the emissivity of a single film layer is low, the film-based bonding force is poor, and the high temperature resistance is poor.

Method used

Multi-arc ion plating, microarc oxidation and hydrothermal treatment processes are used to construct a convex columnar array structure to form a ceramic film layer, and dopant Ti4O7 particles by hydrothermal treatment to improve the emissivity of the film layer.

Benefits of technology

It significantly improves the emissivity, membrane-based binding force and high temperature resistance of the membrane layer, and is suitable for the heat dissipation field of aerospace ionic propulsion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553333A_ABST
    Figure CN119553333A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Ti4O7 doped high-emissivity film layer. The method comprises the following steps: 1, cleaning and drying a substrate; secondly, after the mask plate and the base body are attached, multi-arc ion plating deposition is carried out; 3, micro-arc oxidation; and 4, putting the substrate subjected to micro-arc oxidation into a hydrothermal solution containing Ti4O7 nanoparticles for hydrothermal treatment, and washing, drying and curing to obtain the substrate with the Ti4O7 doped high-emissivity film layer. The composite film layer is prepared by combining multi-arc ion plating, micro-arc oxidation and hydro-thermal treatment processes, the specific surface area and roughness of a matrix are increased by constructing a convex columnar array structure through multi-arc ion plating, and a large number of Ti4O7 nanoparticles are promoted to deposit into the film layer prepared through micro-arc oxidation through hydro-thermal treatment, so that the emissivity of the film layer is greatly improved; and the film is high in film-substrate binding force and high in high-temperature resistance, and is suitable for the field of heat dissipation of key structural parts of aerospace ion electric propulsion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface film layers, and in particular relates to a method for preparing a Ti4O7 doped high-emissivity film layer. Background Art

[0002] Ion electric propulsion technology is one of the most mature space electric propulsion technologies. Compared with chemical propulsion systems, it has the advantages of high specific impulse, low thrust and long working time. It is suitable for deep space exploration, main propulsion of interstellar navigation and other fields. Due to the energy deposition effect, the internal temperature of the ion thruster will be too high when it works in space for a long time. The discharge cavity inside the thruster, namely the upper and lower anode cylinders, will deform and displace due to the high temperature. Excessive thermal deformation will cause serious imbalance of the anode cylinder structure, thereby affecting the discharge performance of the thruster. However, since ion thrusters belong to the category of electric vacuum devices, the heat generated inside the thruster can only be led out through thermal radiation. This requires that the surface of external components such as the screen tube of the thruster must have a high emissivity and long-term high temperature resistance. At present, the external components such as the screen tube of the thruster are mainly made of metal materials such as titanium alloy and aluminum alloy. The emissivity value of the ion thruster itself is relatively low. It is necessary to prepare a high emissivity film on its surface to solve the problem of heat accumulation during long-term operation of ion thrusters.

[0003] At present, the methods for preparing high-emissivity films mainly include plasma spraying, high-temperature sintering, sol-gel, physical vapor deposition, anodizing and micro-arc oxidation. The invention patent with application number 202311322575.0 discloses a high-emissivity rhenium film and its preparation method, which belongs to the field of CVD film preparation technology. The invention regulates the growth orientation of the rhenium film by subjecting the substrate to molten salt corrosion and the deposited sample to chlorine corrosion. The obtained rhenium film has a dense structure, the surface shape of the film is dendritic, has a (002) preferred orientation, and the surface emissivity can reach 0.83. However, the single high-emissivity film preparation method has problems such as poor bonding between the film and the substrate, poor high-temperature resistance of the film, and low emissivity of the film (<0.9). The use of composite surface technology is the direction for preparing high-emissivity films with excellent comprehensive performance. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a Ti4O7 doped high-emissivity film layer in view of the deficiencies of the above-mentioned prior art. The method combines multi-arc ion plating, micro-arc oxidation and hydrothermal treatment processes to prepare a composite film layer. First, a protruding columnar array structure is constructed on the surface of the substrate by multi-arc ion plating to increase the specific surface area and roughness of the substrate. Then, a ceramic film layer is prepared by micro-arc oxidation. Then, a large number of Ti4O7 particles are doped into the ceramic film layer by hydrothermal treatment, which greatly improves the emissivity of the film layer and solves the problems of low emissivity of the existing single film layer, poor film-base bonding, and poor high temperature resistance.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a Ti4O7 doped high emissivity film layer, characterized in that the method comprises the following steps:

[0006] Step 1: Matrix treatment: select titanium alloy or aluminum alloy as the matrix, then clean and dry the matrix to obtain a treated matrix;

[0007] Step 2: Multi-arc ion plating

[0008] Step 201: Use a lock to tightly fit the mask plate with hollow holes to the substrate processed in step 1 to form a combined substrate;

[0009] Step 202, loading the combined substrate in step 201 into a furnace chamber of a multi-arc ion plating furnace, evacuating the chamber, introducing argon gas and increasing the bias voltage, performing particle etching and cleaning on the combined substrate, and then reducing the bias voltage to perform multi-arc ion plating deposition;

[0010] Step 203: After the multi-arc ion plating deposition is completed, the assembled substrate is taken out, and the mask plate with the hollow holes is removed to obtain a densely distributed protruding columnar array structure on the surface of the substrate;

[0011] Step 3: Micro-arc oxidation

[0012] Step 301, preparing electrolyte;

[0013] Step 302, placing the substrate with the protruding columnar array structure in step 203 in the electrolyte prepared in step 301 for micro-arc oxidation;

[0014] Step 4: Hydrothermal treatment

[0015] Step 401, adding deionized water and Ti4O7 nanoparticles into a hydrothermal reaction kettle, and then performing ultrasonic treatment to make the Ti4O7 nanoparticles evenly dispersed in the deionized water to obtain a hydrothermal solution;

[0016] Step 402, washing the substrate after micro-arc oxidation in step 302, placing it in the hydrothermal solution obtained in step 401, and performing hydrothermal treatment by increasing temperature and controlling pressure;

[0017] Step 403: After the hydrothermal treatment is completed, the substrate is taken out, and then rinsed with deionized water and dried and solidified to obtain a substrate with a Ti4O7 doped high-emissivity film layer.

[0018] The above-mentioned method for preparing a Ti4O7 doped high-emissivity film layer is characterized in that the cleaning and drying process in step one is: placing the substrate in an ultrasonic cleaning tank, cleaning it with anhydrous ethanol and deionized water for 15 minutes respectively to remove surface oil and impurities, and then placing it in an oven at 50°C to dry for 10 minutes.

[0019] The above-mentioned method for preparing a Ti4O7 doped high-emissivity film layer is characterized in that the hole diameter of the hollow hole mask plate in step 201 is 20μm to 500μm, the distance between adjacent holes is 10μm to 50μm, and the distance between the lower surface of the hollow hole mask plate and the treated upper surface of the substrate is 50μm to 500μm. The present invention controls the hole diameter of the mask plate to 20μm to 500μm, thereby controlling the diameter of the columnar unit in the raised columnar array structure to ensure that it is larger than the discharge hole diameter of the micro-arc oxidation film layer, thereby ensuring that the micro-arc oxidation film layer can be completely deposited on the surface of the raised columnar array structure; and the size of the distance between adjacent holes ensures that the raised columnar array structure is densely arranged, which is beneficial to increasing the specific surface area of ​​the substrate.

[0020] The above-mentioned method for preparing a Ti4O7 doped high emissivity film layer is characterized in that the vacuum is evacuated to a vacuum degree of 5×10 -4 Pa~5×10 -3 Pa, the flow rate of the introduced argon gas is 15 sccm to 70 sccm, the bias voltage is increased to -1000 V to -600 V, and the particle etching and cleaning time is 5 min to 30 min.

[0021] The above-mentioned method for preparing a Ti4O7 doped high-emissivity film layer is characterized in that the process parameters of the multi-arc ion plating deposition in step 202 are: arc current 30A~90A, bias voltage reduced to -250V~-50V, deposition time 10min~240min, duty cycle 50%~80%, working chamber pressure 0.3Pa~2Pa, deposition temperature 100℃~400℃.

[0022] The above-mentioned method for preparing a Ti4O7 doped high-emissivity film layer is characterized in that the diameter of the columnar unit in the raised columnar array structure in step 203 is 20μm to 500μm, the height is 1μm to 20μm, and the distance between adjacent columnar units is 10μm to 50μm.

[0023] The above-mentioned method for preparing a Ti4O7 doped high-emissivity film layer is characterized in that the electrolyte described in step 301 contains the following components in concentration: sodium silicate 5g / L~30g / L, potassium fluoride 0.1g / L~2g / L, sodium hexametaphosphate 2g / L~20g / L, sodium hydroxide 0.1g / L~2g / L; the process parameters of the micro-arc oxidation described in step 302 are: voltage 400V~600V, duty cycle 10%~50%, frequency 300Hz~1000Hz, time 5min~60min.

[0024] The above-mentioned method for preparing a Ti4O7 doped high-emissivity film layer is characterized in that the concentration of Ti4O7 nanoparticles in the hydrothermal solution in step 401 is 1 g / L to 20 g / L.

[0025] The above-mentioned method for preparing a Ti4O7 doped high-emissivity film layer is characterized in that the temperature of the hydrothermal treatment in step 402 is 120°C to 200°C, the pressure is 200kPa to 1500kPa, and the time is 24h to 72h. The present invention avoids the risk of film cracking and partial shedding by controlling the process parameters of the hydrothermal treatment.

[0026] The above-mentioned method for preparing a Ti4O7 doped high-emissivity film layer is characterized in that the drying and curing in step 403 is a drying treatment at 50°C to 80°C for 2h to 3h, or rapid air drying using compressed air.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] 1. The present invention adopts multi-arc ion plating, and a mask plate with hollow holes is applied to the substrate to construct a raised columnar array structure on the surface of the substrate. This special structure increases the specific surface area and roughness of the substrate, thereby improving the emissivity of the film layer finally formed; at the same time, unlike the doping additives in the traditional micro-arc oxidation process, the raised columnar array structure is equivalent to reconstructing a hole structure on the surface of the substrate, which is beneficial to the deposition of Ti4O7 nanoparticles into the film layer during the subsequent hydrothermal treatment process, thereby increasing the Ti4O7 doping amount and further improving the emissivity of the film layer.

[0029] 2. The present invention uses micro-arc oxidation to form a micro-arc oxidation film layer on the raised columnar array structure on the surface of the substrate. Since the raised columnar array structure is a uniformly arranged array structure, it is beneficial to the formation of a tip discharge effect on the surface of the columnar unit structure during the micro-arc oxidation process, thereby increasing the intensity of the micro-arc oxidation process and improving the bonding strength between the film layer and the substrate.

[0030] 3. The present invention changes the traditional idea of ​​doping metal oxides and nanoparticles in the micro-arc oxidation electrolyte in order to improve the emissivity of the film layer. It proposes to dope Ti4O7 particles in the micro-arc oxidation film layer through hydrothermal treatment, and use high temperature and high pressure to promote the intensified movement of Ti4O7 particles, thereby greatly increasing the doping amount of Ti4O7 particles and depositing them in the discharge holes of the micro-arc oxidation film layer, so that they can better enter the micro-arc oxidation film layer structure, thereby improving the emissivity of the film layer.

[0031] 4. The film layer prepared by the present invention combining multi-arc ion plating, micro-arc oxidation and hydrothermal treatment process has excellent comprehensive performance, with an emissivity of more than 0.9, a film thickness of 5μm to 100μm, a film-base bonding force of more than 40MPa, a film roughness of 1μm to 5μm, and the film layer can withstand 50 thermal cycles between -100℃ and 600℃ without peeling or flaking on the surface. It is suitable for the heat dissipation of key structural parts of aerospace ion electric propulsion.

[0032] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a morphology diagram of the raised columnar array structure prepared on the titanium alloy surface in Example 4 of the present invention. DETAILED DESCRIPTION

[0034] Example 1

[0035] This embodiment includes the following steps:

[0036] Step 1: Matrix treatment: titanium alloy is selected as the matrix, and then the titanium alloy matrix is ​​placed in an ultrasonic cleaning tank, and is cleaned with anhydrous ethanol and deionized water for 15 minutes respectively to remove surface oil and impurities, and then placed in an oven at 50°C for 10 minutes to obtain a treated titanium alloy matrix;

[0037] Step 2: Multi-arc ion plating

[0038] Step 201: Use a lock to tightly fit the mask plate with hollow holes to the titanium alloy substrate processed in step 1 to form a combined substrate; the diameter of the holes in the mask plate with hollow holes is 20 μm, the distance between adjacent holes is 10 μm, and the distance between the lower surface of the mask plate with hollow holes and the upper surface of the processed substrate is 50 μm;

[0039] Step 202: Place the combined substrate in step 201 into a furnace chamber of a multi-arc ion plating furnace and evacuate the chamber to a vacuum degree of 5×10 -3Pa, argon gas was introduced with a flow rate of 15 sccm, and the bias voltage was increased to -600 V, and the assembled substrate was etched and cleaned for 5 min, and then the arc current was set to 30 A, the bias voltage was reduced to -50 V, the deposition time was 10 min, the duty cycle was 50%, the working chamber pressure was 0.3 Pa, and the deposition temperature was 100 ° C, and multi-arc ion plating deposition was performed;

[0040] Step 203, after the multi-arc ion plating deposition is completed, the assembled substrate is taken out, and the mask plate with hollow holes is removed, so as to obtain a uniformly distributed raised columnar array structure on the surface of the titanium alloy substrate; the diameter of the columnar unit in the raised columnar array structure is 20 μm, the height is 1 μm, and the distance between adjacent columnar units is 10 μm;

[0041] Step 3: Micro-arc oxidation

[0042] Step 301, preparing an electrolyte; the electrolyte contains the following components in concentrations: 5 g / L sodium silicate, 0.1 g / L potassium fluoride, 2 g / L sodium hexametaphosphate, and 0.1 g / L sodium hydroxide;

[0043] Step 302, placing the titanium alloy substrate with the protruding columnar array structure in step 203 in the electrolyte prepared in step 301 for micro-arc oxidation, the process parameters of the micro-arc oxidation are: voltage 400V, duty cycle 10%, frequency 300Hz, time 5min;

[0044] Step 4: Hydrothermal treatment

[0045] Step 401, adding deionized water and Ti4O7 nanoparticles into a hydrothermal reaction kettle, and then performing ultrasonic treatment to make the Ti4O7 nanoparticles uniformly dispersed in the deionized water to obtain a hydrothermal solution; the concentration of the Ti4O7 nanoparticles in the hydrothermal solution is 1 g / L;

[0046] Step 402, cleaning the titanium alloy substrate after micro-arc oxidation in step 302 and placing it in the hydrothermal solution obtained in step 401 for hydrothermal treatment, wherein the temperature of the hydrothermal treatment is 120° C., the pressure is 200 kPa, and the time is 24 hours;

[0047] Step 403: After the hydrothermal treatment is completed, the titanium alloy substrate is taken out, and then the surface is rinsed with deionized water, and then dried at 50° C. for 2 hours to obtain a titanium alloy with a Ti4O7 doped high-emissivity film layer.

[0048] After testing, the emissivity of the Ti4O7-doped high-emissivity film layer prepared on the surface of the titanium alloy in this embodiment is 0.9, the film thickness is 6μm, the film bonding strength is 40MPa, the film roughness is 1.2μm, and the film can withstand 50 thermal cycles between -100℃ and 600℃ without peeling or flaking.

[0049] Example 2

[0050] This embodiment includes the following steps:

[0051] Step 1: Matrix treatment: titanium alloy is selected as the matrix, and then the titanium alloy matrix is ​​placed in an ultrasonic cleaning tank, and is cleaned with anhydrous ethanol and deionized water for 15 minutes respectively to remove surface oil and impurities, and then placed in an oven at 50°C for 10 minutes to obtain a treated titanium alloy matrix;

[0052] Step 2: Multi-arc ion plating

[0053] Step 201: Use a lock to tightly fit the mask plate with hollow holes to the titanium alloy substrate processed in step 1 to form a combined substrate; the diameter of the holes in the mask plate with hollow holes is 300 μm, the distance between adjacent holes is 30 μm, and the distance between the lower surface of the mask plate with hollow holes and the upper surface of the processed substrate is 300 μm;

[0054] Step 202: Place the combined substrate in step 201 into a furnace chamber of a multi-arc ion plating furnace and evacuate the chamber to a vacuum degree of 1×10 -3 Pa, argon gas is introduced with a flow rate of 40 sccm, and the bias voltage is increased to -800 V, and the combined substrate is etched and cleaned for 15 minutes, and then the arc current is set to 40 A, the bias voltage is reduced to -150 V, the deposition time is 120 minutes, the duty cycle is 65%, the working chamber pressure is 1 Pa, and the deposition temperature is 250 ° C, and multi-arc ion plating deposition is performed;

[0055] Step 203, after the multi-arc ion plating deposition is completed, the assembled substrate is taken out, and the mask plate with hollow holes is removed, so as to obtain a uniformly distributed raised columnar array structure on the surface of the titanium alloy substrate; the diameter of the columnar unit in the raised columnar array structure is 300 μm, the height is 10 μm, and the distance between adjacent columnar units is 30 μm;

[0056] Step 3: Micro-arc oxidation

[0057] Step 301, preparing an electrolyte; the electrolyte contains the following components in concentrations: 15 g / L sodium silicate, 1 g / L potassium fluoride, 10 g / L sodium hexametaphosphate, and 1 g / L sodium hydroxide;

[0058] Step 302, placing the titanium alloy substrate with the protruding columnar array structure in step 203 in the electrolyte prepared in step 301 for micro-arc oxidation, the process parameters of the micro-arc oxidation are: voltage 500V, duty cycle 30%, frequency 600Hz, time 30min;

[0059] Step 4: Hydrothermal treatment

[0060] Step 401, adding deionized water and Ti4O7 nanoparticles into a hydrothermal reaction kettle, and then performing ultrasonic treatment to make the Ti4O7 nanoparticles uniformly dispersed in the deionized water to obtain a hydrothermal solution; the concentration of the Ti4O7 nanoparticles in the hydrothermal solution is 10 g / L;

[0061] Step 402, cleaning the titanium alloy substrate after micro-arc oxidation in step 302 and placing it in the hydrothermal solution obtained in step 401 for hydrothermal treatment, wherein the temperature of the hydrothermal treatment is 160° C., the pressure is 700 kPa, and the time is 48 hours;

[0062] Step 403, after the hydrothermal treatment is completed, the titanium alloy substrate is taken out, and then the surface is rinsed with deionized water, and then dried at 65°C for 2.5 hours to obtain a titanium alloy with a Ti4O7 doped high emissivity film layer.

[0063] After testing, the emissivity of the Ti4O7-doped high-emissivity film layer prepared on the surface of the titanium alloy in this embodiment is 0.92, the film thickness is 11μm, the film bonding strength is 43MPa, the film roughness is 1.8μm, and the film can withstand 50 thermal cycles between -100℃ and 600℃ without peeling or flaking.

[0064] Example 3

[0065] This embodiment includes the following steps:

[0066] Step 1: Matrix treatment: an aluminum alloy is selected as the matrix, and then the aluminum alloy matrix is ​​placed in an ultrasonic cleaning tank, and is cleaned with anhydrous ethanol and deionized water for 15 minutes respectively to remove surface oil and impurities, and then placed in an oven at 50° C. for 10 minutes to obtain a treated aluminum alloy matrix;

[0067] Step 2: Multi-arc ion plating

[0068] Step 201: Use a lock to tightly fit the mask plate with hollow holes to the aluminum alloy substrate processed in step 1 to form a combined substrate; the diameter of the holes in the mask plate with hollow holes is 500 μm, the distance between adjacent holes is 50 μm, and the distance between the lower surface of the mask plate with hollow holes and the upper surface of the processed substrate is 500 μm;

[0069] Step 202: Place the combined substrate in step 201 into a furnace chamber of a multi-arc ion plating furnace and evacuate the chamber to a vacuum degree of 5×10 -4 Pa, argon gas is introduced with a flow rate of 70 sccm, and the bias voltage is increased to -1000 V, and the assembled substrate is etched and cleaned for 30 min, and then the arc current is set to 90 A, the bias voltage is reduced to -250 V, the deposition time is 240 min, the duty cycle is 80%, the working chamber pressure is 2 Pa, and the deposition temperature is 400 ° C, and multi-arc ion plating deposition is performed;

[0070] Step 203, after the multi-arc ion plating deposition is completed, the assembled substrate is taken out, and the mask plate with hollow holes is removed, so as to obtain a uniformly distributed raised columnar array structure on the surface of the aluminum alloy substrate; the diameter of the columnar unit in the raised columnar array structure is 500 μm, the height is 20 μm, and the distance between adjacent columnar units is 50 μm;

[0071] Step 3: Micro-arc oxidation

[0072] Step 301, preparing an electrolyte; the electrolyte contains the following components in concentrations: 30 g / L sodium silicate, 2 g / L potassium fluoride, 20 g / L sodium hexametaphosphate, and 2 g / L sodium hydroxide;

[0073] Step 302, placing the aluminum alloy substrate with the protruding columnar array structure in step 203 in the electrolyte prepared in step 301 for micro-arc oxidation, the process parameters of the micro-arc oxidation are: voltage 600V, duty cycle 50%, frequency 1000Hz, time 60min;

[0074] Step 4: Hydrothermal treatment

[0075] Step 401, adding deionized water and Ti4O7 nanoparticles into a hydrothermal reaction kettle, and then performing ultrasonic treatment to make the Ti4O7 nanoparticles uniformly dispersed in the deionized water to obtain a hydrothermal solution; the concentration of the Ti4O7 nanoparticles in the hydrothermal solution is 20 g / L;

[0076] Step 402, washing the aluminum alloy substrate after micro-arc oxidation in step 302 and placing it in the hydrothermal solution obtained in step 401 for hydrothermal treatment, wherein the temperature of the hydrothermal treatment is 200° C., the pressure is 1500 kPa, and the time is 72 hours;

[0077] Step 403: After the hydrothermal treatment is completed, the aluminum alloy substrate is taken out, and then the surface is rinsed with deionized water, and then quickly dried with compressed air to obtain an aluminum alloy with a Ti4O7 doped high-emissivity film layer.

[0078] After testing, the emissivity of the Ti4O7-doped high-emissivity film layer prepared on the surface of the titanium alloy in this embodiment is 0.95, the film thickness is 20μm, the film bonding strength is 45MPa, the film roughness is 2.1μm, and the film can withstand 50 thermal cycles between -100℃ and 600℃ without peeling or flaking.

[0079] Example 4

[0080] This embodiment includes the following steps:

[0081] Step 1: Matrix treatment: an aluminum alloy is selected as the matrix, and then the aluminum alloy matrix is ​​placed in an ultrasonic cleaning tank, and is cleaned with anhydrous ethanol and deionized water for 15 minutes respectively to remove surface oil and impurities, and then placed in an oven at 50° C. for 10 minutes to obtain a treated aluminum alloy matrix;

[0082] Step 2: Multi-arc ion plating

[0083] Step 201: Use a lock to tightly fit the mask plate with hollow holes to the aluminum alloy substrate processed in step 1 to form a combined substrate; the diameter of the holes in the mask plate with hollow holes is 100 μm, the distance between adjacent holes is 50 μm, and the distance between the lower surface of the mask plate with hollow holes and the upper surface of the processed substrate is 50 μm;

[0084] Step 202: Place the combined substrate in step 201 into a furnace chamber of a multi-arc ion plating furnace and evacuate the chamber to a vacuum degree of 5×10 -4 Pa, argon gas is introduced with a flow rate of 60 sccm, and the bias voltage is increased to -1000 V, and the assembled substrate is etched and cleaned for 30 min, then the arc current is set to 80 A, the bias voltage is reduced to -250 V, the deposition time is 200 min, the duty cycle is 80%, the working chamber pressure is 2 Pa, and the deposition temperature is 400 ° C, and multi-arc ion plating deposition is performed;

[0085] Step 203: After the multi-arc ion plating deposition is completed, the assembled substrate is taken out, and the mask plate with the hollow holes is removed to obtain a uniformly distributed protruding columnar array structure on the surface of the aluminum alloy substrate, such as Figure 1 As shown, the uniformity of the raised columnar array structure is good; the diameter of the columnar unit in the raised columnar array structure is 100 μm, the height is 20 μm, and the distance between adjacent columnar units is 50 μm;

[0086] Step 3: Micro-arc oxidation

[0087] Step 301, preparing an electrolyte; the electrolyte contains the following components in concentrations: 20 g / L sodium silicate, 2 g / L potassium fluoride, 20 g / L sodium hexametaphosphate, and 2 g / L sodium hydroxide;

[0088] Step 302, placing the aluminum alloy substrate with the protruding columnar array structure in step 203 in the electrolyte prepared in step 301 for micro-arc oxidation, the process parameters of the micro-arc oxidation are: voltage 500V, duty cycle 50%, frequency 800Hz, time 40min;

[0089] Step 4: Hydrothermal treatment

[0090] Step 401, adding deionized water and Ti4O7 nanoparticles into a hydrothermal reaction kettle, and then performing ultrasonic treatment to make the Ti4O7 nanoparticles uniformly dispersed in the deionized water to obtain a hydrothermal solution; the concentration of the Ti4O7 nanoparticles in the hydrothermal solution is 15 g / L;

[0091] Step 402, washing the aluminum alloy substrate after micro-arc oxidation in step 302 and placing it in the hydrothermal solution obtained in step 401 for hydrothermal treatment, wherein the temperature of the hydrothermal treatment is 200° C., the pressure is 1500 kPa, and the time is 72 hours;

[0092] Step 403: After the hydrothermal treatment is completed, the aluminum alloy substrate is taken out, and then the surface is rinsed with deionized water, and then quickly dried with compressed air to obtain an aluminum alloy with a Ti4O7 doped high-emissivity film layer.

[0093] After testing, the emissivity of the Ti4O7-doped high-emissivity film layer prepared on the surface of the titanium alloy in this embodiment is 0.94, the film thickness is 41μm, the film bonding strength is 44MPa, the film roughness is 2.6μm, and the film can withstand 50 thermal cycles between -100℃ and 600℃ without peeling or flaking.

[0094] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a Ti4O7 doped high emissivity film layer, characterized in that: The method comprises the following steps: Step 1: Matrix treatment: select titanium alloy or aluminum alloy as the matrix, then clean and dry the matrix to obtain a treated matrix; Step 2: Multi-arc ion plating Step 201: Use a lock to tightly fit the mask plate with hollow holes to the substrate processed in step 1 to form a combined substrate; Step 202, loading the combined substrate in step 201 into a furnace chamber of a multi-arc ion plating furnace, evacuating the chamber, introducing argon gas and increasing the bias voltage, performing particle etching and cleaning on the combined substrate, and then reducing the bias voltage to perform multi-arc ion plating deposition; Step 203: After the multi-arc ion plating deposition is completed, the assembled substrate is taken out, and the mask plate with the hollow holes is removed to obtain a densely distributed protruding columnar array structure on the surface of the substrate; Step 3: Micro-arc oxidation Step 301, preparing electrolyte; Step 302, placing the substrate with the protruding columnar array structure in step 203 in the electrolyte prepared in step 301 for micro-arc oxidation; Step 4: Hydrothermal treatment Step 401, adding deionized water and Ti4O7 nanoparticles into a hydrothermal reaction kettle, and then performing ultrasonic treatment to make the Ti4O7 nanoparticles evenly dispersed in the deionized water to obtain a hydrothermal solution; Step 402, washing the substrate after micro-arc oxidation in step 302, placing it in the hydrothermal solution obtained in step 401, and performing hydrothermal treatment by increasing temperature and controlling pressure; Step 403: After the hydrothermal treatment is completed, the substrate is taken out, and then rinsed with deionized water and dried and solidified to obtain a substrate with a Ti4O7 doped high-emissivity film layer.

2. The method for preparing a Ti4O7 doped high emissivity film layer according to claim 1, characterized in that: The cleaning and drying process in step 1 is as follows: the substrate is placed in an ultrasonic cleaning tank, and cleaned with anhydrous ethanol and deionized water for 15 minutes respectively to remove surface oil and impurities, and then placed in an oven at 50° C. to dry for 10 minutes.

3. The method for preparing a Ti4O7 doped high emissivity film layer according to claim 1, characterized in that: In step 201 , the hole diameter of the mask plate with hollow holes is 20 μm to 500 μm, the distance between adjacent holes is 10 μm to 50 μm, and the distance between the lower surface of the mask plate with hollow holes and the upper surface of the processed substrate is 50 μm to 500 μm.

4. The method for preparing a Ti4O7 doped high emissivity film layer according to claim 1, characterized in that: The vacuum in step 202 is evacuated to a vacuum degree of 5×10 -4 Pa~5×10 -3 Pa, the flow rate of the introduced argon gas is 15 sccm to 70 sccm, the bias voltage is increased to -1000 V to -600 V, and the particle etching and cleaning time is 5 min to 30 min.

5. The method for preparing a Ti4O7 doped high emissivity film layer according to claim 1, characterized in that: The process parameters of the multi-arc ion plating deposition in step 202 are: arc current 30A~90A, bias voltage reduced to -250V~-50V, deposition time 10min~240min, duty cycle 50%~80%, working chamber pressure 0.3Pa~2Pa, deposition temperature 100℃~400℃.

6. The method for preparing a Ti4O7 doped high emissivity film layer according to claim 1, characterized in that: In step 203 , the diameter of the columnar unit in the protruding columnar array structure is 20 μm to 500 μm, the height is 1 μm to 20 μm, and the distance between adjacent columnar units is 10 μm to 50 μm.

7. The method for preparing a Ti4O7 doped high emissivity film layer according to claim 1, characterized in that: The electrolyte in step 301 contains the following components in concentration: sodium silicate 5g / L~30g / L, potassium fluoride 0.1g / L~2g / L, sodium hexametaphosphate 2g / L~20g / L, sodium hydroxide 0.1g / L~2g / L; the process parameters of micro-arc oxidation in step 302 are: voltage 400V~600V, duty cycle 10%~50%, frequency 300Hz~1000Hz, time 5min~60min.

8. The method for preparing a Ti4O7 doped high emissivity film layer according to claim 1, characterized in that: The concentration of Ti4O7 nanoparticles in the hydrothermal solution in step 401 is 1 g / L to 20 g / L.

9. The method for preparing a Ti4O7 doped high emissivity film layer according to claim 1, characterized in that: The temperature of the hydrothermal treatment in step 402 is 120° C. to 200° C., the pressure is 200 kPa to 1500 kPa, and the time is 24 h to 72 h.

10. The method for preparing a Ti4O7 doped high emissivity film layer according to claim 1, characterized in that: The drying and curing in step 403 is drying at 50° C. to 80° C. for 2 h to 3 h, or rapid air drying using compressed air.

Citation Information

Patent Citations

  • High-emissivity rhenium coating and preparation method thereof

    CN117364052A